CeDaD—a novel assay for simultaneous tracking of cell death and division in a single population - Lukas Nöltner; Kurt Engeland; Robin Kohler (Cell Death Discovery)
Abstract The cell division cycle and the various forms of programmed cell death are interconnected. A prominent example is the tumor suppressor p53, which not only induces apoptosis but also plays an important role in the arrest of the cell cycle. Consequently, simultaneous analysis of cell division and cell death is frequently of significant interest in cell biology research. Traditionally, these processes require distinct assays, making concurrent analysis challenging. To address this, we present a novel combined assay, called CeDaD assay—Cell Death and Division assay—which allows for the simultaneous quantification of cell division and cell death within a single-cell population. This assay utilizes a straightforward flow cytometric approach, combining a staining based on carboxyfluorescein succinimidyl ester (CFSE) to monitor cell division with an annexin V-derived staining to assess the extent of cell death.